154 Empaglifozin on cardiac energetics and function. (4th June 2021) - Thirunavukarasu, Sharmaine; Jex, Nicholas; Chowdhary, Amrit; Hassan, Imtiaz; Straw, Sam; Broadbent, David; Swoboda, Peter; Witte, Klaus; Cubbon, Richard; Greenwood, John; Plein, Sven; Levelt, Eylem
Abstract : Background: Type 2 diabetes (T2D) is associated with an increased risk of heart failure (HF) and cardiovascular (CV) mortality. Sodium–glucose-cotransporter-2 (SGLT2) inhibitors reduce the risk of major adverse CV events and hospitalization for HF in T2D patients with high cardiovascular risk, despite only a modest improvement in glycaemic control. Restoring cellular energy homeostasis and reversing adverse cardiac remodelling in diabetes have been speculated as a potential metabolic modulatory effect of SGLT2 inhibitors leading to their beneficial CV outcomes. Myocardial energy deficient states can be detected non-invasively by 31-phosphorus magnetic resonance spectroscopy (31P-MRS). Objectives: Utilising cardiovascular magnetic resonance imaging (CMR) and 31P-MRS in a single centre longitudinal cohort study, we aimed to investigate the effects of the selective SGLT2 inhibitor empagliflozin on myocardial energetics, function, perfusion, and myocardial cellular volume in patients with T2D. Methods: Eighteen consecutive T2D patients who were commenced on empagliflozin in cardiometabolic optimisation clinics underwent CMR and 31P-MRS scans before and after twelve-week empagliflozin treatment, and plasma N-terminal pro hormone B-type natriuretic peptide (NT-proBNP) levels were measured. ( Table 1 ) Ten controls with no diabetes underwent an identical 31P-MRS and CMR protocol on a single visit. Results: When compared to controls, patients with T2D showed: lower myocardial energetics (1.52±0.40 vs 2.20±0.5, p=0.0005), lower stress myocardial blood flow (1.60±0.50 vs 2.10±0.50, p=0.02) and lower left ventricular ejection fraction (52±13% vs 63±4%, p=0.01). Treatment with empagliflozin led to significant improvements in myocardial energetics (PCr/ATP: 1.52 to 1.76, p=0.009). This was accompanied by a relative 13% improvement in left ventricular ejection fraction (p=0.001), 3% improvement in global longitudinal strain (p=0.01), 61% reduction in NTproBNP (p=0.05), and 9% reduction in myocardial cell volume (p=0.04). No significant change in myocardial blood flow or diastolic strain was detected ( table 1 ) . Conclusions: Empagliflizon improves myocardial energetics and function, reduces myocardial cellular volume, and reduces NT-proBNP levels in patients with T2D ( figure 1 ) . This study, by using the myocardial phosphocreatine to ATP ratio to monitor the early energetic response of the heart to treatment, and CMR to monitor structural and functional changes, provides significant novel insights into potential mechanisms by which empagliflozin exerts its beneficial cardiovascular effects. Conflict of Interest: NONE